DETERMINAN AKUNTABILITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH DI KOTA JAYAPURA - Cornelia Desiana Matani; Novalia H. Bleskadit (Universitas Cenderawasih, 2023)
The objective of this study is to analyses the determinants of the financial management accountability of school operational fund (BOS hereafter) in Jayapura municipality, Papua province. The research method used was a survey with questionnaires. Quantitative analysis using the SPSS analysis tool was used to analyze the data collected in order to test empirically the factors that influence accountability of the management of BOS funds in beneficiary schools in Jayapura City. The results showed that the BOS funds received in Jayapura Municipality in 2019 and 2020 amounted to 24.9 billion which were managed in 14 junior high schools and 54 elementary schools. BOS spending consists of personnel spending, goods and services spending, and capital spending. Data collected from 242 respondents showed that the factors of Transparency, HR Quality, Organizational Commitment, Internal Control System had an effect on the Accountability of BOS funds. The results of the research are to provide empirical factors on the accountable management of BOS funds so that they become technical knowledge for other districts/cities in Papua Province and others in managing their BOS Fund and other public transfer funds.